Clinical significance of postoperative pulmonary complications in elderly patients with lung cancer. (30th May 2022) - Okada, Satoru; Shimomura, Masanori; Ishihara, Shunta; Ikebe, Satoshi; Furuya, Tatsuo; Inoue, Masayoshi
Abstract: OBJECTIVES: An increasing number of elderly patients with impaired immunity, malnutrition and comorbidities are considered surgical candidates. This study aimed to clarify the predictive factors and prognostic impact of postoperative pulmonary complications in elderly patients with lung cancer. METHODS: This retrospective study included 188 patients (≥75 years) who underwent complete anatomical lung resection for non-small cell lung cancer between 2005 and 2019. Postoperative pulmonary complications graded ≥II in the Clavien-Dindo classification, occurring within 30-day post-surgery were evaluated. Multivariate logistic regression analyses and Cox proportional hazard models were used to analyse predictors and prognostic impact of complications. RESULTS: Video-assisted thoracoscopic surgery was performed in 154 patients (81.9%). The 90-day mortality rate was 0.5%. Postoperative pulmonary complications including air leak, pneumonia, sputum retention, atelectasis, bronchopleural fistula and empyema occurred in 29 patients (15.4%). A lower prognostic nutritional index (<45) and longer operative time were independent predictive factors of pulmonary complications, with 33.3% of patients experiencing both factors. Following a median follow-up of 48 months, the 5-year overall and relapse-free survival rates were significantly worse in patients with pulmonary complications than in those without them (54.4% vs 81.5% and 41.2% vs 74.9%). Pulmonary complications were significantly associated with worse overall and relapse-free survival [hazard ratio (95% confidence interval): 1.97 (1.01–3.66), P  =   0.047 and 2.35 (1.28–4.12), P  =   0.007, respectively] along with pathologic stage and carcinoembryonic antigen levels. CONCLUSIONS: Postoperative pulmonary complications are associated with a lower prognostic nutritional index and prolonged operative time; the complications are independent adverse prognostic factors in elderly patients. Abstract : Lung cancer is the leading cause of cancer-related death worldwide [1], and surgical resection remains the standard treatment for localized diseases.